The Role of School Principals’ Transformational Leadership in Enhancing Teachers’ Motivation and Pedagogical Competence: A Case Study at SDN Gunting I, Sukorejo - Suprihatin, Rahayu; Harris, Taufiq; Faizin, A.; Rimadani, Eprilia (The Future of Education Journal, 2026)
This study aims to analyze the transformational leadership of school principals in enhancing teachers’ motivation and pedagogical competence at SDN Gunting I, Sukorejo District. The study employs a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and documentation, involving the school principal and teachers as informants. Data analysis was conducted using the interactive model proposed by Miles and Huberman. The findings indicate that the principal’s transformational leadership is manifested through the development of a shared vision, the provision of motivation and role modeling, and reflective academic supervision. These leadership practices contribute to increased teacher work motivation and the strengthening of pedagogical competence in the teaching and learning process. This study contributes to the development of educational leadership scholarship and offers practical implications for strengthening leadership in elementary schools